THE EFFECT OF GIVING HEALTH EDUCATION ABOUT CATARACT ON THE INTENTION TO HAVE CATARACT SURGERY OF CATARACT CLIENT IN PUSKESMAS SEMBORO JEMBER - Siswoyo Siswoyo (UNEJ e-Proceeding, 2017)
Background: Cataract is the turbidity of the eye lens that causes impaired vision. This occured because of the damage on the eye lens so it reduced eye vision. Indonesia is still recorded as the highest number of patients with cataract in South East Asia, Therefore, surgical cataract or cataract surgery becomes the most surgical done by an ophthalmologist. However there is a gap between the incidences of cataract with the number of surgeries in a year. The gap between the number of cataract patients who were operated on and were not operated because it was lack of intention to have surgery from cataract patients themselves. The lack of intention from the patients to have cataract surgery could be caused by several factors, such as the lack of access to information and knowledge. The increasing of knowledge was closely related to the provision of health education, and the health education was provided, patients with cataract can improve his or her intention to have cataract surgery. Methods: This research used a pre-experimental research design by using study design One-group pre-post test design. This sampling technique was a non-probability sampling, total sampling (sampling saturated) with a total sample of 25 respondents. Results: The result of data analysis used a dependent t-test and p-value was 0,000. P value indicated <α (0,05) which meant there was the effect of health education about cataract to the intention on having cataract surgery. Conclusions: The result was expected to increase information and improve knowledge of cataract that could increase the client's intention to have cataract surgery. Keywords: cataract, intention, health education